Relationship Between Vocabulary Size And MUET Score Of Malaysian ESL Undergraduates - Shamsudin, Sarimah; Lateh, Nor Hazwani Munirah; Attan, Anie (Universiti Sains Malaysia, 2016)

(untitled)
Vocabulary is an important element of a language. Without the knowledge of vocabulary, people will not be able to understand what others are saying to them. Furthermore, they will also experience difficulty expressing what they intend to say or write. Taking this into account, language learners are required to achieve a certain attainment of vocabulary size of a target language to ensure they are able to meet the demands of the language and achieve maximum comprehension when the language is used in communication. As such, it is very important for language learners to be aware of their vocabulary size of the target language. To this end, the current study was conducted to identify the English vocabulary size of first year undergraduate students in a Malaysian public university. In addition, it aims to examine whether there is a correlation between the scores which the students obtained for their Malaysian University English Test (MUET) and their total English vocabulary size. An intact group of thirty first year students (19 female, 11 male) who use English as their second language participated in the study. The Vocabulary Size Test (VST) by Nation and Beglar (2007) was administered to gauge their English vocabulary size and a questionnaire was used to elicit demographic details. The findings revealed that majority of the participants have below than 4000 English vocabulary size. The mean score of the participants’ English vocabulary size is 3183 word families indicating that the participants on average do not reach the vocabulary size of 6000 to 9000 word families to achieve 98% coverage in written and spoken English texts (Nation, 2006). Their minimum English vocabulary size is 2200 whereas the maximum is 4500 word families. A strong positive correlation of r=0.84 was found with regard to the relationship between the participants’ MUET score and their English vocabulary size. This result suggests that the better the participants’ score in MUET, the more English vocabulary they would have. This result could also mean that the larger the English vocabulary size of the participants, the higher their MUET score is.